2005
DOI: 10.1212/01.wnl.0000180969.03719.81
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal speech sound representation in persistent developmental stuttering

Abstract: Individuals with persistent developmental stuttering have abnormal permanent traces for speech sounds, and their abnormal speech sound representation may underlie their speech disorder. The link between abnormal speech neural traces of the auditory cortex and speech disfluency supports the relevance of speech perception mechanisms to speech production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 44 publications
7
36
0
2
Order By: Relevance
“…Participants were presented with a protocol to evaluate central sound representation (49), that comprised three different conditions tapping general acoustic perception (duration, frequency, and pattern conditions) and specific language perception (phonetic condition) (see Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…Participants were presented with a protocol to evaluate central sound representation (49), that comprised three different conditions tapping general acoustic perception (duration, frequency, and pattern conditions) and specific language perception (phonetic condition) (see Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…Pinsky and McAdam (1980) obtained the opposite profile, also nonsignificant. Most evoked response potential (ERP) studies of other components in stuttering did not find, or did not look for, abnormal hemispheric asymmetry (Corbera, Corral, Escera, & Idiazabal, 2005;Cuadrado & Weber-Fox, 2003;Rosanowski et al, 1998;Vartanov, Glozman, Kisel'nikov & Karpova, 2005;Weber-Fox, Spencer, & Spruill, 2004). Morgan, Cranford, and Burk (1997) presented common (80% probability) versus rare (20% probability) auditory tones to people who stutter and to fluent speakers, requiring no response.…”
Section: Introduction Eeg Investigations Of Stutteringmentioning
confidence: 99%
“…Many nonmotoric anomalies may contribute to dysfluent speech. For example, dysfluent speakers manifest abnormal attention (Bosshardt, 2006;Bosshardt, Ballmer, & de Nil, 2002;Heitmann, Asbjornsen, & Helland, 2004), abnormal short-term memory (Hakim & Ratner, 2004;Vartanov et al, 2005) and abnormal visual and auditory speech perception (Corbera et al, 2005;Cuadrado & WeberFox, 2003;Rosanowski et al, 1998;WeberFox et al, 2004). Thus, it is important to focus on all these aspects in the search for brain based direct contributions to stuttering.…”
Section: Introduction Eeg Investigations Of Stutteringmentioning
confidence: 99%
“…1 Decades of neuroimaging research have revealed various functional and structural anomalies in people with PDS. [2][3][4][5][6][7][8][9][10] However, these studies cannot differentiate between neural anomalies that are responsible for PDS and those that are a result of compensating for stuttering. 8,9 This is because long-term compensation can result in both functional and structural changes in the brain of PDS patients.…”
mentioning
confidence: 99%